One-Pot Efficient Synthesis of Sulfonimidamides from Sulfonyl Chloride - Ma, Shi-Wei; Huang, Jin; Ma, Long-jun; Li, Guang-xun (Synlett, 2025)
Sulfonimidamides, featuring a hexavalent sulfur structure, are a class of key compounds with broad application prospects in the fields of pharmaceuticals and agrochemicals. However, their applications have been limited due to the lack of economically effective synthetic methods. Utilizing the cost-effective and readily accessible sulfonyl chloride as the initial reagent, this method involves the sequential formation of intermediates, including sulfinamide and sulfonimidoyl chloride, culminating in the synthesis of the sulfonylimidamide compounds. This approach yields sulfonimidamides in moderate to good yields, thereby offering a viable synthetic route for the expanded application of these important compounds.
Keywords: one-pot strategy; sulfonimidamide; sulfonyl chloride; sulfinamide; sulfonimidoyl chloride